The African writer between two languages: reflections of a toubab - Kalinowska, Ewa (Literatūra, 2023)
The choice of language for literary creation is not a simple one, especially for African writers. Having grown up in a naturally multilingual environment and exposed to European languages, they often express themselves in the language of former colonizers. However, this is neither obvious nor should it remain a definitive choice for authors from various African countries. We will present different motivations, attitudes, and decisions of several writers; from the most radical, rejecting the European language, to others who hold onto it – either exclusively or accompanied by African languages.